Microwave-Assisted Synthesis of Porous Biomolecule-Incorporated Metal-Organic Frameworks as Efficient Nanocarriers for Anti-Cancer Drugs - Nguyen, Trang Thi Thu; Le, Bao Quang Gia; Nguyen, Vy Tran Hanh; Lee, Jae-Hyoung; Mai, Ngoc Xuan Dat; Nguyen, Linh Ho Thuy; Doan, Tan Le Hoang (WILEY-V C H VERLAG GMBH, 2023)
Biomolecule-incorporated metal-organic frameworks (b-MOFs) exhibit enhanced bioavailability and biocompatibility, making them an ideal option for use as drug delivery vehicles. While b-MOFs possess outstanding drug loading and release capabilities, their microscale crystal sizes restrict their applicability as nanocarriers and drug delivery systems. To overcome this limitation, this paper presents a microwave-irradiation-based technique for the synthesis of porous adenine-incorporated Zn-based MOFs with particle sizes of approximately 200 nm as paclitaxel nanocarriers. The nanomaterial demonstrated a substantial paclitaxel loading capacity of 637 mg g(-1). Moreover, it effectively increased the solubility of paclitaxel by 2.5-fold compared to that of the free form. Thus, the nano MOF is a promising delivery vehicle for paclitaxel. Notably, the paclitaxel-loaded nano MOF exhibited higher toxicity toward cancer cells than the free drug, further highlighting its potential as an effective anticancer agent.